SYNTHESIS AND ELECTRICAL PROPERTIES OF (Li, Ca)-SUBSTITUTED LANTHANUM COBALTATES: DOI: https://doi.org/10.17721/1728-2209.2018.1(55).5 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
(Li, Ca)-substitute lanthanum cobaltates with composition La1-3xLixCа2xCoO3-δ (0≤x≤0.33) was synthesized by co-precipitation method of hydroxycarbonates. It is determined that the homogeneity region for the system La1-3xLixCа2xCoO3-δ is limited to the composition of x = 0,1. As in the case of Sr- and Ba-containing cobaltates, at x> 0.1, peaks on the diffractograms of the compounds correspond to the phase of lithium cobaltite Li1-yCoO2 with a layered structure. It turned out that the crystallographic parameters of orthorhombic Ca-containing cobaltates increases in comparison with the parameters of the unsubstituted LaCoO3.It is found that with an increase in the mean ion radius of the substituent in the region of homogeneity there is an increase in the average oxidation state of cobalt. The morphological characteristics of complex oxides were studied by using scanning electron microscopy. The grain sizes are in the range from 1 to 2 microns. In the photo along with the small grains you can notice enough large sintered particles in the size of 3 – 4 microns. Also, in SEM-photos, it is possible to detect the impurity phase of lithium cobaltate in the form of grains of the correct hexagonal form, which confirms the results of the X-Ray phase analysis.The 3d-hole (Co4+) formed by the adding of a small amount of Ca2+ and Li+ remains bound to adjacent closely spaced cobalt ions and acts as deep acceptor levels. With increasing substitution degree x, the acceptor complexes interact, forming an σ * conduction band. Due to this, at x≥0.3, the conductivity section of the semiconductor type disappears at the temperature dependence of the electric resistance and the conductivity begins to take a metallic character. On the other hand, contributing to the overall resistance of the system may introduce impurity phases, which is more likely, taking into account the results of the X-Ray phase analysis. It should also be noted that when the concentration of additives increases, the steepness of the curves ρ(Т) decreases.
Keywords: co-precipitation method; substituted lanthanum cobaltates; semiconductor-metal transition